Comparing Visions of Justice: Rawls’ Idealism vs. Sen’s Pragmatism - Tirkey, C. Anupa (Integrated Journal for Research in Arts and Humanities, 2023)
John Rawls and Amartya Sen are two of the most influential figures in contemporary political philosophy, offering distinct and often contrasting approaches to justice. Rawls' A Theory of Justice lays the foundation for "justice as fairness," emphasizing principles designed under a "veil of ignorance" to ensure impartiality in institutional arrangements. Sen’s The Idea of Justice, on the other hand, critiques Rawls’ idealism and advocates for a practical, outcome-oriented approach centered on comparative justice and the capabilities of individuals. This paper explores the philosophical debate between Rawls and Sen, analyzing their shared goals, points of divergence, and implications for addressing contemporary global challenges, such as economic inequality, climate change, and democratic governance.